Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada Al Mubarak Cendekia Islamic School - Jamaluddin, Sitti Lathifah; Mashur Razak; Sujatmiko (Jurnal Online Manajemen ELPEI, 2026)
This study aims to analyze the influence of compensation and work environment on employee performance through job satisfaction as an intervening variable at Al Mubarak Cendekia Islamic School. This study uses a quantitative approach with a survey method. Data was obtained through the distribution of questionnaires to employees of Al Mubarak Cendekia Islamic School. Data analysis was carried out using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4 software to test the direct and indirect relationships between the research variables. The results of the study show that (1) Compensation has a positive and significant effect on employee performance at Al Mubarak Cendekia Islamic School. (2) The work environment has a positive and insignificant effect on employee performance at Al Mubarak Cendekia Islamic School. (3) Job satisfaction has a positive and significant effect on employee performance at Al Mubarak Cendekia Islamic School. (4) Compensation has a positive and significant effect on job satisfaction at Al Mubarak Scholar Islamic School. (5) The work environment has a positive and significant effect on job satisfaction at Al Mubarak Cendekia Islamic School. (6) Compensation has a positive and significant effect on employee performance through job satisfaction at Al Mubarak Cendekia Islamic School. (7) The work environment has a positive and significant effect on employee performance through job satisfaction at Al Mubarak Cendekia Islamic School. Keywords : Compensation, Work Environment, Employee Performance, Job Satisfaction.